Analysis of the Differentially Expressed Genes Induced by Cisplatin Resistance in Oral Squamous Cell Carcinomas and Their Interaction - Wu, Hua-Tao; Chen, Wen-Tian; Li, Guan-Wu; Shen, Jia-Xin; Ye, Qian-Qian; Zhang, Man-Li; Chen, Wen-Jia; Liu, Jing (Frontiers in Genetics, 2020)
Background: Oral squamous cell carcinoma (OSCC) is a solid tumor, which originates from squamous epithelium, with about 400,000 new-cases/year worldwidely. Presently, chemoradiotherapy is the most important adjuvant treatment for OSCC, mostly in advanced tumors. However, clinical resistance to chemotherapy still leads to poor prognosis of OSCC patients. Via high-throughput analysis of gene expression database of OSCC, we investigated the molecular mechanisms underlying cisplatin resistance in OSCC, analyzing the differentially expressed genes (DEGs) and their regulatory relationship, to clarify the molecular basis of OSCC chemotherapy resistance and provide a theoretical foundation for the treatment of patients with OSCC and individualized therapeutic targets accurately. Methods: Datasets related to “OSCC” and “cisplatin resistance” (GSE111585 and GSE115119) were downloaded from the GEO database and analyzed by GEO2R. Venn diagram was used to obtain drug-resistance-related DEGs. Functional enrichment analysis and Kyoto encyclopedia of genes and genomes (KEGG) pathway analysis were performed on DEGs using The Database for Annotation, Visualization and Integrated Discovery (DAVID) software. Protein-protein interaction (PPI) network was constructed by STRING (search tool for recurring instances of neighbouring genes) database. Potential target genes of miRNA were predicted via miRDB, and cBioportal was used to analyze the function and survival of the potential functional genes. Results: 48 upregulated DEGs and 49 downregulated DEGs were obtained from the datasets, with cutoff as p <0.01 and |log FC| > 1. The DEGs in OSCC mainly enriched in cell proliferation regulation, and chemokine activity. In PPI network with hub score > 300, the hub genes were identified as NOTCH1, JUN, CTNNB1, CEBPA, and ETS1. Among miRNA-mRNA targeting regulatory network, hsa-mir-200c-3p, hsa-mir-200b-3p, hsa-mir-429, and hsa-mir-139-5p were found to simultaneously regulate multiple hub genes. Survival analysis showed that patients with high CTNNB1 or low CEBPA expression had poor outcome. Conclusions: In the OSCC cisplatin-resistant cell lines, NOTCH1, JUN, CTNNB1, CEBPA, and ETS1 were found as the hub genes involved in regulating the cisplatin resistance of OSCC. Members of the miR-200 family may reverse drug resistance of OSCC cells by regulating the hub genes, which can act as potential targets for the treatment of OSCC patients with cisplatin resistance.